2018
DOI: 10.1002/mds.27319
|View full text |Cite|
|
Sign up to set email alerts
|

Ataxia‐telangiectasia: A review of movement disorders, clinical features, and genotype correlations

Abstract: Ataxia-telangiectasia is an autosomal recessive neurodegenerative disorder that was initially thought to present exclusively in childhood. With the discovery of the ATM gene, the phenotypic spectrum of the condition has expanded. This review elaborates the expanded phenomenology, including oculomotor apraxia and immunodeficiency, and estimates the presence of each movement disorder feature from previously reported literature. Initial manifestations of Ataxia-telangiectasia include cerebellar symptoms (67%), dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
14

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 43 publications
1
95
0
14
Order By: Relevance
“…Furthermore, we highlight the potential role of p84-NBN protein conserving the primordial FHA domain, which we showed to be also present in previously reported NBN-related infertile patients (Warcoin et al, 2009), and which could explain their mild phenotype. Exploration of such hypomorphic variants widens the field of medical genetics to many common and mild human disorders, such as ATM hypomorphic variants and tremor or parkinsonism (Fievet, Bellanger, Rieunier et al, 2019;Levy & Lang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we highlight the potential role of p84-NBN protein conserving the primordial FHA domain, which we showed to be also present in previously reported NBN-related infertile patients (Warcoin et al, 2009), and which could explain their mild phenotype. Exploration of such hypomorphic variants widens the field of medical genetics to many common and mild human disorders, such as ATM hypomorphic variants and tremor or parkinsonism (Fievet, Bellanger, Rieunier et al, 2019;Levy & Lang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the association of cerebellar structural abnormalities and dystonia observed in both humans and mice lacking RIMBP1 supports the increasingly recognized role of cerebellar dysfunction in dystonia pathogenesis. For example, dystonia is increasingly recognized as one of the main presentation of several disorders in which pathology primarily involves the cerebellum, including ataxia-telangiectasia (33) and several autosomal dominant spinocerebellar ataxias (34). More mechanistically, recent work in mice showed that abnormal and irregular burst firing of Purkinje cells, as well as in neurons in the deep cerebellar nuclei, can be observed in several mouse models of dystonia (35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Ataxia-telangiectasia (at) is a rare neurodegenerative disease that results in cerebellar ataxia, oculomotor abnormalities, telangiectasias, immune deficiency, sinopulmonary infections, radiosensitivity, and an elevated risk of cancer [6][7][8][9][10][11][12] . Individuals affected by at are most prone to lymphoid malignancies in childhood, but they are also at risk for developing epithelial cancers later in life 7 .…”
Section: Pathophysiology and Clinical Presentationmentioning
confidence: 99%